Editor’s Comments - Judith A. Holton (Grounded Theory Review: An International Journal)
It is my privilege to serve as Editor-in-Chief and present this new issue of The Grounded Theory Review. I am delighted to introduce our international panel of peer review editors who will work with me to ensure that all papers submitted are promptly reviewed with comments provided back to the authors. All are experienced grounded theorists who will also contribute their own work to the journal from time to time.